Accounting Application on Financial Statements Based on SAK EMKM at Save and Loan Cooperatives in Karangasem Regency - N M Ari Meliana Sativa Sandi; Jeni Susanti; I Dewa Made Mahayana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
In 2009 IAI has issued SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability), but in 2018 IAI issued a new policy for entities without public accountability and micro, small and medium income, known as the Financial Accounting Standards for Micro Small and Medium Entities. Savings and loan cooperatives are one of the entities that are classified as micro, small and medium entities because they have complied with Law no. 20 of 2008 about Micro, Small and Medium Enterprises. The research using the Financial Statements of Savings and Loan Cooperatives in Karangasem Regency. Researchers took 30 savings and loan cooperatives for the samples. This study uses purposive sampling to determine the suitability between the financial statements consisting of the Balance Sheet, Report on Calculation of Remaining Operating Results and Notes on Financial Statements. The data collection method in this study used the questionnaires or structured interviews and uses descriptive analysis techniques to determine the application of accounting in preparing the financial statements of savings and loan cooperatives in Karangasem Regency. Standard-compliant theory is compared with the content of financial statements. According to the study of the application of the financial statements for savings and loan cooperatives in Karangasem Regency with SAK EMKM are very good. From the weighted score, the results obtained 82% where the scale is at 76% - 100% on the Guttman scale, that’s known by financial statements of savings and loan cooperatives in Karangasem Regency are very in accordance with SAK EMKM.